Treatment of clinical mastitis in sheep with locally prepared drugs - Aljudi, A. M. H. (The Iraqi Journal of Veterinary Medicine, 1999)
Mastitis were diagnosed in (80) ewes depending on clinical examination , California mastitis test , & bacterial isolates include: Staph. aureus, Strept. agalactica , Strept. dys agalactica , E. coli, & Bacillas spp. The infected ewes were treated by using locally prepared intra mammary preparations ; first group received Amoxicillin & hydrocortison with (76.7)% cure rate ; the second group received Ampicillin & hydrocortisone with (73.3) % cure rate ; while the third group received a commercial preparation ( Masticlox ® ) with (75)% cure rate.